2022
DOI: 10.3390/jrfm15050192
|View full text |Cite
|
Sign up to set email alerts
|

The Profitability of Technical Analysis during the COVID-19 Market Meltdown

Abstract: This article explores the profitability of technical trading rules around the COVID-19 pandemic market meltdown for the S&P 500 index, Bitcoin, Comex gold spot, crude oil WTI, and the VIX. Trading rule profits are estimated from January to May 2020, including three sub-periods, on a high-frequency data set. The results reveal that the trading rules can beat the buy-and-hold trading strategy. However, only the Bollinger Bands and trading range break-out rules become profitable after transaction costs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
8
0
1
Order By: Relevance
“…Additionally, López-Martn, Benito Muela, and Arguedas [37] demonstrated that, while the EMH has been challenged over time, changes in Bitcoin markets show a tendency to evolve from less to more efficiency, indicating that other cryptocurrencies may be less explored than Bitcoin but also appear understudied in relevant studies. Furthermore, some trading rules may create a considerable excess return for most cryptocurrencies other than Bitcoin, meaning that cryptocurrency markets may not be efficient for most cryptocurrencies other than Bitcoin [38]. We then infer that the aforementioned result may be attributable to Bitcoin's appeal to individual investors, institutional investors, and even academics, thereby enhancing the efficiency of the Bitcoin market.…”
Section: Of 18mentioning
confidence: 89%
“…Additionally, López-Martn, Benito Muela, and Arguedas [37] demonstrated that, while the EMH has been challenged over time, changes in Bitcoin markets show a tendency to evolve from less to more efficiency, indicating that other cryptocurrencies may be less explored than Bitcoin but also appear understudied in relevant studies. Furthermore, some trading rules may create a considerable excess return for most cryptocurrencies other than Bitcoin, meaning that cryptocurrency markets may not be efficient for most cryptocurrencies other than Bitcoin [38]. We then infer that the aforementioned result may be attributable to Bitcoin's appeal to individual investors, institutional investors, and even academics, thereby enhancing the efficiency of the Bitcoin market.…”
Section: Of 18mentioning
confidence: 89%
“…We generate the automated trading signals using two of the most frequently applied technical indicators, namely moving average convergence divergence (MACD) [25] and Bollinger bands (BB) [26], and a hybrid strategy that reinforces these two with fractal dimension (D) [27]. Academic studies have widely investigated the performance of MACD and BB as technical trading strategies, either as a single indicator or combined indicators [9,[28][29][30][31]. For example, Xie et al [31] found that MACD performs better than other trend-following indicators, such as dual moving average (MA) crossover and average directional index (ADX).…”
Section: Fractal Analysis and Technical Indicatorsmentioning
confidence: 99%
“…For example, Xie et al [31] found that MACD performs better than other trend-following indicators, such as dual moving average (MA) crossover and average directional index (ADX). Lento and Gradojevic [29] showed that, out of a set of technical indicators tested, BB appears as the only technical indicator that is profitable during the market crash. In detecting market phases, there are variations or more sophisticated techniques that utilize fractals or the Hurst exponent, such as multifractal detrended fluctuation analysis (MF-DFA) by Kantelhardt et al [32].…”
Section: Fractal Analysis and Technical Indicatorsmentioning
confidence: 99%
“…Regarding this point, the research of Lento and Gradojevic (2022) is relevant. They explored the profitability of technical trading rules (including the traditional moving average cross-over rule) around the COVID-19 pandemic market crash (from January to May 2020) for five asset markets (bitcoin, gold, oil, and so on).…”
Section: Published By Sciedu Pressmentioning
confidence: 99%